Factors Associated with Pesticide Exposure and Relationship with the Incidence of Anemia - Hotman Natama Nainggolan; Fitria Saftarina; Soedjarwo, Soedjarwo (CV. AFDIFAL MAJU BERKAH, 2023)
The use of pesticides by farmers from year to year has increased. Excessive use can harm human health because it is toxic and less persistent in nature. every year as many as one million people will experience health problems due to pesticides and the prevalence continues to increase. There are many impacts resulting from exposure to pesticides including anemia which is a form of chronic effects from the use of pesticides (WHO, 2017). This systematic review aims to analyze and examine various literature that discusses anemia that occurs in farmers due to pesticides. The research method used is literature review with secondary data obtained from the Google Scholar database, PubMed with a span of 10 years. In order to obtain 8 scientific articles that can be analyzed. The results of a literature review of 8 research articles show that most farmers control pests on plants using pesticides. Factors that influence the incidence of anemia are not using PPE, duration of spraying, years of service, nutritional status, level of education, gender, exposure to pesticides. Human health is also an impact that is affected by excessive and continuous use and exposure to pesticides, especially for the farmers themselves. The body exposed to pesticides causes abnormalities in the blood profile because the pesticides themselves interfere with the organs that form blood cells and the body's immune system.